Effect of Leafflower (Phyllanthus niruri Linn.) treatment on kidney and uterus in sodium chloride -induced fibrotic rats - Khairil Pahmi; M. Sidratullah (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
Background. Phyllanthus niruri (local name : meniran) extract is utilized in treating kidney and uterus disease. Effects of ethanol extract of P. niruri on kidney and uterus of 2% NaCl triggered fibrotic rats had been studied. Aim of Study. Aim of this study to explore the effect of leafflower (Phyllanthus niruri Linn.) treatment on kidney and uterus in 2% NaCl - induced fibrotic rats. Methods. Wistar rats were challenged with 2% NaCl in drinking water to induce fibrotic kidney and uterus. Phyllanthus niruri extract (200 mg/kg) was given orally for 4 weeks. Matrix extracellular abundance was determined by HE Staining and measured by METAVIR Fibrosis Score. The results of this study were assayed by SPSS 16. Results. P. niruri extract was potent to reduce the matrix extracellular in 2% NaCl-induced rats compared to control group (p<0.05). Conclusion. P. niruri extract was potent to decrease the matrix extracellular in the kidney and uterus of the rats.